Использование новых жировых ингредиентов в производстве хлебобулочных изделий - Калина, В. С.; Мыколенко, С. Ю.; Луценко, М. В. (НТУ "ХПИ", 2014)
В статье приведены результаты исследований влияния жировых ингредиентов (нерафинированное и рафинированное жирное кориандровое масло) на качество хлебобулочных изделий, также описаны зависимости характеристик готовой продукции от различного процентного внесения исследуемых рецептурных компонентов. Установлено методом бальной оценки, что использование нерафинированного и рафинированного жирного кориандрового масла в технологии хлебобулочных изделий оказывает влияние на органолептические показатели готовых изделий и структурно-механические свойства мякиша. Стандартными методами определены физико-химические показатели хлебобулочных изделий (влажность, кислотность, пористость). Из.: 2. Библиогр.: 12.

It has been shown results of usage off at ingredients (crude and refined oil fatty coriander) for bakery production. Depending on the characteristics of the finished products from different content off at ingredients was described. According to a numericals core the using of crude and refined fatty coriander oil in bakery technology affects on the organoleptic characteristics off in is hed products and rheological properties of the crumb. Physico-chemical parameters of bakery products (moisture, acidity, porosity) has been identified by standard methods. On the basis of this facts, as well same organoleptic and expert evaluations of samples of bakery products can be recommended for inclusion in the formulation of production 5% refined oil fatty coriander. This improves the taste, color and aroma of the finished baking, improving its physical and chemical characteristics. The same should be to recommend the use in the formulations of bakery products is refined oil fatty coriander that enriches finished products in un saturated fatty acid sand makes a variety of daily human diet.
Using of new fat ingredients for bakery production
Keywords: пищевые продукты; жирные кориандровые масла; жирные кислоты; органолептические показатели; биологическая ценность; bakery products; fatty coriander oil; fatty acids